2001
DOI: 10.1046/j.1365-2265.2001.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between low‐dose (1 µg), standard‐dose (250 µg) ACTH stimulation tests and insulin tolerance test in the evaluation of hypothalamo–pituitary–adrenal axis in primary fibromyalgia syndrome

Abstract: We conclude that the perturbation of the HPA axis in PFS is characterized by underactivation of the HPA axis. Some patients with PFS may have subnormal adrenocortical function. LDT is more sensitive than SDT or ITT in the investigation of the HPA axis to determine the subnormal adrenocortical function in patients with PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…It has been suggested that the 1 g ACTH test is more sensitive than a 250 μg ACTH test in the assessment of HPA axis activity. 21,22 In the present study, we found that both basal cortisol values and peak cortisol responses during LDT, SDT and ITT in AS patients were comparable to those in healthy controls. In contrast to findings in other inflammatory diseases such as rheumatoid arthritis and polymyalgia rheumatica, there is no apparent abnormality of HPA axis activity in patients with AS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It has been suggested that the 1 g ACTH test is more sensitive than a 250 μg ACTH test in the assessment of HPA axis activity. 21,22 In the present study, we found that both basal cortisol values and peak cortisol responses during LDT, SDT and ITT in AS patients were comparable to those in healthy controls. In contrast to findings in other inflammatory diseases such as rheumatoid arthritis and polymyalgia rheumatica, there is no apparent abnormality of HPA axis activity in patients with AS.…”
Section: Discussionsupporting
confidence: 71%
“…ITT has been accepted as the gold standard for the assessment of adrenal insufficiency. 20 We recently 21 evaluated the HPA axis of 16 patients with primary fibromyalgia syndrome and found that 6 out of the 16 patients had subnormal adrenal cortisol responses, which were revealed by LDT but not by SDT or ITT. It has been suggested that the 1 g ACTH test is more sensitive than a 250 μg ACTH test in the assessment of HPA axis activity.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, studies that assess more than a single aspect of HPA axis function in the same group of patients are quite rare, as are studies that evaluate the same HPA response to several different tests [334,339,340,353,360,363,364]. This makes it difficult to discern a response pattern and to pinpoint the precise point within the HPA axis Metyrapone inhibits the 11β-hydroxylase enzyme that catalyzes the conversion of 11-deoxycortisol to cortisol in the adrenal gland and, therefore, results in increased ACTH release from the pituitary [622] DST dexamethasone suppression test where the defect occurs.…”
Section: Stress the Hpa Axis And The Autonomic Nervous Systemmentioning
confidence: 99%
“…An alternative explanation for differential suppression at the pituitary and adrenal levels in FMS might involve effects of dexamethasone on ACTH-independent factors known to regulate adrenocortical activity, that is, autonomic innervation, immune input, or intra-adrenal peptides [46][47][48]. Enhanced direct and indirect feedback affecting the adrenal cortex might plausibly contribute to hypocortisolism in FMS and might in part explain reduced adrenocortical responsiveness to ACTH 1-24 stimulation in FMS [10,11]. Clearly, future studies are needed to specifically scrutinize the various pathways of adrenal regulation in FMS.…”
Section: Fmsmentioning
confidence: 99%
“…In the corticotropin-releasing factor (CRF) stimulation test, patients with FMS exhibit increased adrenocorticotropin (ACTH) but normal cortisol responses, suggesting sensitization of the pituitary in combination with adrenal insufficiency [7][8][9]. Reduced cortisol secretion has also been observed in response to ACTH 1-24 stimulation in FMS [10,11], although negative results have been reported as well [8]. Many of these findings are consistent with relative hypocortisolism in FMS.…”
Section: Introductionmentioning
confidence: 99%